The Realization of the Myth of Death and Rebirth (in the Play “July” by Ivan Vyrypaev) - Kurant, Elena (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2013)
This article concerns Russian modern drama, exactly the work of one of its most world famous representatives – Ivan Vyrypaev, 37-year-old actor, theatre and film director and playwright. The drama July by Ivan Vyrypaev is seen in relation to the ritual practices, which are a part of the myth of death and rebirth. Based on contemporary studies of ritual and mythological theory in literature the author identifies in the text of drama a kind of special ‘mifomir’– a structure with its sacred space and time, with the liminal stage of existence of a priest, who is at the same time a victim of a ritual sacrifice in the name of the renewal of life and restoring the cosmos out of chaos. This way of reading contemporary drama reveals her attempt to indicate the relations of the modern man with the eternal values and reflects an attempt to determine the identity and the limits of human being.